Genetic and Physiological Adaptations of Marine Bacterium Pseudomonas stutzeri 273 to Mercury Stress - Zheng, Rikuan; Wu, Shimei; Ma, Ning; Sun, Chaomin (Frontiers in Microbiology, 2018)
Mercury-mediated toxicity remains one of the greatest barriers against microbial survival, even though bacterial resistance to mercury compounds can occur. However, the genetic and physiological adaptations of bacteria to mercury stress still remains unclear. Here, we show that the marine bacterium P. stutzeri 273 is resistant to 50 µM Hg2+ and removes up to 94% Hg2+ from culture. Using gene homologous recombination and complementation, we show that genes encoding Hg2+-transport proteins MerT, MerP, the mercuric reductase MerA and the regulatory protein MerD, but not mer regulator MerR, are essential for bacterial mercuric resistance when challenged with Hg2+. Further, mercury stress inhibits flagellar development, motility, chemotaxis and biofilm formation of P. stutzeri 273, which are verified by transcriptomic and physiological analyses. Surprisingly, we discover that MerF, a previously reported Hg2+-transporter, determines flagellar development, motility and biofilm formation in P. stutzeri 273 by genetic and physiological analyses. Our results strongly indicate that MerF plays an integral role in P. stutzeri 273 to develop physiological responses to mercury stress. Notably, MerF homologues are also prevalent in different human pathogens. Using this unique target may provide novel strategies to control these pathogenic bacteria, given the role of MerF in flagella and biofilm formation. In summary, our data provide an original report on MerF in bacterial physiological development and suggest that the mer in marine bacteria has evolved through progressive, sequential recruitment of novel functions over time.